Churchill at Chartwell - Fedden, Robin, 1908-1977 (Pergamon Press, 1969)
Churchill at Chartwell is an account of Winston Churchill's years at Chartwell, his home at Kent from 1924 until his death in January 1965 at the age of ninety. This book traces Churchill's relationship with the house and its contents, particularly the garden. It chronicles the events of his career as they emerge from Chartwell or reflect upon it. This book is comprised of six chapters and begins with a background on Chartwell, from the time Churchill bought it in 1922 and his move, together with his family, to the place in 1924, until his death. The next chapter discusses the changes made by.